2013
DOI: 10.1007/s13738-013-0382-6
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of mixtures of nitrophenols using multivariate curve resolution-alternating least squares

Abstract: A simple procedure for the quantitative determination of mixtures of nitrophenols pollutants in environmental and biological samples based on continuous spectrophotometric acid-base titrations and multivariate curve resolution has been proposed. The procedure simultaneously takes into account the spectroscopic and acidbase properties of the nitrophenols, which leads to a higher selectivity. The quantitative determination of analyte in the presence of unknown and uncalibrated interferences is a general benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…He has concluded that the phosphorus contains herbicides (e.g., glyphosate) can stimulate soil microbial growth [40]. Biodegradation of nitro group-based herbicides can easily do in the presence of PGPR by converting the nitro group into amine group [18,22,25,63].…”
Section: Effect Of Molecule 1 On Pgpr Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…He has concluded that the phosphorus contains herbicides (e.g., glyphosate) can stimulate soil microbial growth [40]. Biodegradation of nitro group-based herbicides can easily do in the presence of PGPR by converting the nitro group into amine group [18,22,25,63].…”
Section: Effect Of Molecule 1 On Pgpr Strainsmentioning
confidence: 99%
“…Various author have noticed that many amino acid and nitro derivatives have medicinal values including the antimicrobial and antifungal activities [15,18,21,22,24,25,44,52,63].…”
Section: Effects Of Molecule1 On Pathogenic Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, MCR-ALS is characterized by a bilinear decomposition of an original data matrix (D) into two matrices [31][32][33][34][35][36][37][38][39][40][41][42][43]: i) a matrix corresponding to the concentration profiles (C) and; ii) a second matrix related to the pure spectra profiles (S). MCR model can be expressed as D = CS T + ε, where the matrix D (dimensions m different individual spectra by n intensities measured at each spectral points) is approximated by the product of the matrix C (dimensions k components in the different by m rows of the data matrix) and matrix S T (transpose of matrix pure spectral profiles of dimensions k components by n columns of the original data matrix); and ε is the matrix of residuals (dimensions m different individual spectra by n intensities) containing the information not explained by the model.…”
Section: Introductionmentioning
confidence: 99%
“…MCR-ALS is extensively employed in several technological issues related with the quantitation antibacterial agents presented water samples [44], determination of furosemide in the presence of interfering agent (anti-inflammatory flufenamic acid) [45], quantitative determination of sulfur [32], sulfonamide drugs in biomedical analysis [46], mixtures of nitrophenols pollutants in environmental and biological samples [34], proteinaceous binders in medieval paints [37], antioxidants (butylatedhydroxytoluene and N,N′-di-secbutyl-p-phenylenediamine) in biodiesel blends [41] and concentration profiles in milk lactic acid fermentation [33]; enzymatic determination of levodopa and carbidopa in pharmaceuticals [47], measurements of the relative amounts of different iron oxide and oxyhydroxides present in the passive films [48], interpretation of the kinetic behavior of the photochemical degradation process of decabromodiphenyl ether [43] and photodynamics of salicylidene aniline in ultrafast competitive photoreactions [38].…”
Section: Introductionmentioning
confidence: 99%